Research of embedding algorithm for wireless network virtualization - Bin CAO; Shi-chao XIA; Fang HE; Yun LI (Tongxin xuebao)
Wireless network virtualization has become one of the promising techniques in fifth generation mobile networks (5G),and the virtual network embedding plays a very important role.A model was formulated to describe the problem and a wireless virtual network embedding algorithm based on joint bandwidth and power allocation (WVNEA-JBP) was put forward,which selected the suitable node and path to serve the data transmission from virtual networks.In order to minimize the overhead while satisfy the higher capacity request,this algorithm considered the impact of interference of wireless links and supports path splitting.A case study was introduced to show how WVNEA-JBP to work.Furthermore,simulation results show that WVNEA-JBP is able to accomplish the efficient utilization of network resources and improve the accept rate of virtual network requests.